1994
DOI: 10.1109/94.368657
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of prebreakdown VI characteristics of a wire-plate electrostatic precipitator operating under combined dc-pulse energization

Abstract: With the advent of pulse energization in electrostatic precipitators, the need for developing a model to simulate the physical processes in the prebreakdown region, at which the precipitator normally operates, is also increasing. The development of such a model helps in predicting the V I characteristics of a precipitator, which will be important to diagnose the electrical problems associated with the precipitator during its operation. The paper reports the details of a proposed model t o predict the V I chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The ionization and attachment coefficients can well be represented by the equations of the type [20,21]:…”
Section: The Current-voltage Characteristicsmentioning
confidence: 99%
“…The ionization and attachment coefficients can well be represented by the equations of the type [20,21]:…”
Section: The Current-voltage Characteristicsmentioning
confidence: 99%
“…The modelling of electrostatic precipitator (ESP) has been the subject of many papers [7][8][9][10][11][12][13], but none has used the method of experimental designs which proved to be a good tool for the optimization of such processes. The method used in this paper is to determine a mathematical model for the ESP process of a laboratory model, which will be used to determine optimal values of process factors and also for predicting the outcome of the process for randomly values of the factors.…”
Section: Introductionmentioning
confidence: 99%
“…This new estimate of the total space charge density on the conductor's surface along with the new estimate of E are again used in (21) and (22) to get a new estimate of s ρ on all of the finite element nodes. This process continues and a self-consistent solution is assumed to be obtained when the maximum variation in φ and ρ in two consecutive iterations does not exceed a pre-specified value ( 2 δ taken as 0.1% in this work).…”
Section: B Boundary Conditionsmentioning
confidence: 99%
“…Cristina and Feliziani [19] proposed a procedure for the numerical computation of the electric field and current density distributions in a dc electrostatic precipitator in the presence of dust, taking into account the particle-size distribution. The performance of WDEP s under impulse voltages has been investigated by many researchers [20][21][22][23][24][25][26]. It has been reported that the application of a pulse energization to electrostatic precipitators has substantial benefits when high resistivity particulate materials are involved.…”
Section: Electrode Misalignment Induced Malfunctionsmentioning
confidence: 99%